First record of the genus Sulorgilus van Achterberg (Hymenoptera: Braconidae: Orgilinae) from Vietnam and China, with description of a new species - Long, Khuat Dang; Achterberg, Cornelis van (Academia Journal of Biology, 2016)
Sulorgilus van Achterberg, 1994, is recorded for the first time from Vietnam and China. It is a monotypic genus of the subfamily Orgilinae (Hymenoptera: Braconidae) with one species described from Sulawesi (Indonesia). A new species, Sulorgilus devriesi Long & van Achterberg, sp. n., is described and illustrated. A key to the species of the genus Sulorgilus is added.